Rhetoric in Debt - Sharp-Hoskins, Kellie, 1982- (Book collections on Project MUSE., 2023)
"Examines the relationship between rhetoric and debt, arguing that they are fundamentally entangled in producing and disciplining who is deemed worthy of credit and how debt materializes differentially: as a credit to some and condemnation of others"--